Protective effects of morin and propolis against cytarabine-induced neurotoxicity: a multi-biomarker approach - Bag, Hakan; Yilmaz, Seval; Ceribasi, Songul (De Gruyter Poland Sp Z O O, 2026)
Cytarabine (Cyt) is a cornerstone chemotherapeutic agent for acute myeloid leukemia (AML) and various hematological malignancies. This study sought to investigate the neuroprotective potential of morin and propolis against Cyt-induced neurotoxicity. Forty-two Sprague Dawley rats were randomly assigned to six groups: control, morin (200 mg/kg/day), propolis (100 mg/kg/day), Cyt (100 mg/kg/day), morin + Cyt, and propolis + Cyt. Biochemical analysis of brain tissue revealed that Cyt administration significantly elevated malondialdehyde (MDA) levels and glutathione-S-transferase (GST) activity, while depleting catalase (CAT) and glutathione peroxidase (GSH-Px) activities. Immunohistochemical findings showed that Cyt increased 8-hydroxydeoxyguanosine (8-OHdG) and B-cell lymphoma/leukemia-2-associated X protein (Bax) expression, whereas it downregulated Glutathione peroxidase 4 (GPX4) and B-cell lymphoma/leukemia-2 (Bcl-2). Treatment with morin or propolis effectively reversed these oxidative and apoptotic markers, as evidenced by decreased MDA and Bax levels, alongside increased activities of antioxidant enzymes. Furthermore, the histopathological alterations induced by Cyt were markedly ameliorated by both antioxidants. These results suggest that Cyt-induced neuronal degeneration is driven by oxidative stress and apoptosis, processes that can be mitigated by morin and propolis supplementation.
Keywords: cytarabine; neurotoxicity; morin; propolis; apoptosis